Drying kinetics and its influence on the dimensions of shelled pumpkin seeds - Vieira, Danise Medeiros; Barros, Sâmela Leal; Silva, Vírgínia Mirtes de Alcântara; Santos, Newton Carlos; Nascimento, Amanda Priscila Silva; Melo, Mylena Olga Pessoa (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
The drying applied to pumpkin seeds, increases the shelf life of the product and consequently facilitates its marketing. The objective of this study was to perform the drying kinetics of shelled pumpkin seeds at different drying air temperatures, adjusting the experimental data obtained to empirical mathematical models and to evaluate the influence of drying on their dimensions. Drying kinetics of peeled pumpkin seeds were performed at different drying air temperatures (50, 70 and 90 °C), adjusting the experimental data obtained to the empirical mathematical models of Handerson and Pabis, Lewis and Page. Seed size was analyzed for length, width and thickness using a digital caliper. Regarding the applied mathematical models, the Page model was considered to be more efficient in describing the drying process of shelled pumpkin seeds. It was found that the seed dimensions were directly influenced by the increase of the drying temperature. Therefore, increasing the temperature of the applied drying air provided greater moisture removal from the product and its size data can be used to size the size of sieves and postharvest equipment.